Cytogenetic effects of insecticide Lamda cyhalothrin on meristemic cells of Allium cepa L. (Baghdad Science Journal, 2008)
The effect of insecticide lamda cyhalothrin on Allium cepa L.root meristem were studied cytogenetically .Using three concentrations of the insecticide 5%, 7.5%, 10% at 6,12,24hours treatments . The insecticide significantly reduced the mitotic index at all concentrations. Moreover showed its ability to induced C – metaphase in 10% .The effects were also caused chromosome aberration like stickness in anaphase, telophase, binucleated cells, Micronuclei formation. These alternations indicating that this insecticide was effective in producing disturbance of spindle fibers.